The Superiority of Willpower over Firepower: A Philosophical Analysis of Vietnamese Resistance against the United States, 1954–1975 - Riyanto Wujarso; Muhammad Arif Saifudin; Joni Widjayanto (LPPM Institut Pendidikan Nusantara Global, 2026)
The Vietnam War (1954–1975) stands as a crucial case study of asymmetric conflict, where a major military superpower (the US) was defeated by an ideologically grounded resistance movement. This research specifically argues that Vietnam’s victory was a classic case of the superiority of willpower over firepower. The study’s primary objective is to analyze the essence and implementation of the